Structural performance and analysis of asymmetrically skewed and curved ultra-high performance fibre reinforced concrete slabs. (1st February 2022) - Mohamed Ali, M.S.; Mahdi, S.; Sheikh, A.H.; Elchalakani, M.; Xie, T.
Highlights: Skewed and curved ultra-high performance fibre-reinforced concrete slabs tested. Influence of skewness and curvature on slabs are studied. Energy-based theories used to develop closed-form solutions to both slab systems. Detailed numerical model made using damage modelling to assess response of slabs. Abstract: The present study investigates the structural performance of asymmetrically skewed and curved ultra high-performance fibre-reinforced concrete (UHPFRC) slabs/bridge decks through both experimental and theoretical investigations. Four slabs were constructed with varying skew and curvature angles and tested under increasing concentrated loading. In addition to the experimental program, closed-form models based on the method of virtual work and Castigliano's second theorem were developed to predict the reaction forces and deflections at the mid-span of the skewed and curved slabs within the linear elastic state. Closed-form solutions were developed based on yield-line theory in conjunction with a mechanics-based moment-rotation model to predict deflections at the ultimate state, and a thorough finite-element analysis implementing non-linear material models in conjunction with damage modelling was performed to observe the full-range structural performance of the slabs. A parametric study was performed to examine the effect of skew and curvature angle on deflection, shear, bending and torsion. The generic analytical procedures and finite-element model were compared against experimental results obtained from the study and results show that the models can be applied to UHPFRC asymmetrically skewed and curved slabs.